Radio frequency energy harvesting circuits design for the applications of low power electronics. Issue 1 (2nd January 2022) - Banerjee, Joydeep; Banerjee, Subhasish
ABSTRACT: Radio frequency (RF) energy harvesting, a new demanding area of research during last decade promises to be a source of generating a small amount of electrical power to drive low power consumable electronics devices. This paper presents different RF energy harvesting circuits and techniques to improve the performance of RF energy harvesting technology. A multiport Wilkinson power combiner circuit followed by Villard voltage multiplier circuit has been achieved to combine output power from multiple RF input sources. The performance of a multiport Schottky diode-based energy harvesting circuit is also studied. Experimentally RF power is captured at different frequencies. A Monte Carlo simulation along with worst case analysis has been carried out and results show close proximity to the nominal or actual outcome. A multiport NMOS-based Dickson's charge pump is also designed compatible with MOS fabrication technology which shows remarkable results.